3D cell-printing of tendon-bone interface using tissue-derived extracellular matrix bioinks for chronic rotator cuff repair. (2nd April 2021) - Chae, Suhun; Sun, Yucheng; Choi, Yeong-Jin; Ha, Dong-Heon; Jeon, Inho; Cho, Dong-Woo
Abstract: The tendon-bone interface (TBI) in rotator cuffs exhibits a structural and compositional gradient integrated through the fibrocartilaginous transition. Owing to restricted healing capacity, functional regeneration of the TBI is considered a great clinical challenge. Here, we establish a novel therapeutic platform based on 3D cell-printing and tissue-specific bioinks to achieve spatially-graded physiology for functional TBI regeneration. The 3D cell-printed TBI patch constructs are created via a spatial arrangement of cell-laden tendon and bone-specific bioinks in a graded manner, approximating a multi-tissue fibrocartilaginous interface. This TBI patch offers a cell favorable microenvironment, including high cell viability, proliferative capacity, and zonal-specific differentiation of encapsulated stem cells for TBI formation in vitro . Furthermore, in vivo application of spatially-graded TBI patches with stem cells demonstrates their regenerative potential, indicating that repair with 3D cell-printed TBI patch significantly accelerates and promotes TBI healing in a rat chronic tear model. Therefore, our findings propose a new therapeutic strategy for functional TBI regeneration using 3D cell-printing and tissue-specific decellularized extracellular matrix bioink-based approach.